2024
DOI: 10.1038/s41562-024-01814-x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic computational phenotyping of human cognition

Roey Schurr,
Daniel Reznik,
Hanna Hillman
et al.

Abstract: Computational phenotyping has emerged as a powerful tool for characterizing individual variability across a variety of cognitive domains. An individual’s computational phenotype is defined as a set of mechanistically interpretable parameters obtained from fitting computational models to behavioural data. However, the interpretation of these parameters hinges critically on their psychometric properties, which are rarely studied. To identify the sources governing the temporal variability of the computational phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 84 publications
(135 reference statements)
0
6
0
Order By: Relevance
“…However, applying our approach to clinical populations or studies interested in individual differences would particularly benefit from more stable estimates. Among many factors that impact reliability, Schurr et al (2024) identify random noise in behavioral measurements that could arise from discrepancies given the current application of the slider. Improvements to the slider design, including cues about previous estimates (to reduce motor noise) and modifying the starting point of the slider (requiring fewer adjustments), could increase the overall reliability of the parameters.…”
Section: Discussionmentioning
confidence: 99%
“…However, applying our approach to clinical populations or studies interested in individual differences would particularly benefit from more stable estimates. Among many factors that impact reliability, Schurr et al (2024) identify random noise in behavioral measurements that could arise from discrepancies given the current application of the slider. Improvements to the slider design, including cues about previous estimates (to reduce motor noise) and modifying the starting point of the slider (requiring fewer adjustments), could increase the overall reliability of the parameters.…”
Section: Discussionmentioning
confidence: 99%
“…This was in line with the task design, as stability in task performance is maintained by adjusting in task difficulty, which increased across sessions. In addition to practice factors, affective state can be a source of significant temporal variability in cognitive task performance 35 . However, we did not measure any changes in affective state or psychiatric symptoms across time.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, a less pessimistic view of poor reliability among cognitive outcomes is that behavioural tasks provide legitimate estimates of momentary cognitive capacities when tested, but these are liable to fluctuations over time 34 . In line with this, cognitive capacities tend to temporally covary with affect and practice factors, which are often not accounted for in reliability assessments 35 . This further illustrates the need for within-subject longitudinal assessments in computational psychiatry, to infer individual clinical and cognitive phenotypes.…”
Section: Introductionmentioning
confidence: 87%
“…This suggests that the practice effects of computational psychiatry assays offer rich set of additional phenotypic information. Indeed, a recent study utilizing a battery of seven behavioral tasks over twelve weekly sessions found both pronounced practice affects, and that affective state significantly impacted on task behavior (Schurr et al, 2024).…”
Section: Test Reliabilitymentioning
confidence: 99%